2006
DOI: 10.1007/s11434-006-1431-7
|View full text |Cite
|
Sign up to set email alerts
|

Hydrotalcite-supported Pd-Cu catalyst for nitrate adsorption and reduction from water

Abstract: Hydrotalcite-supported Pd-Cu catalyst for nitrate adsorption and catalytic reduction from water is prepared by co-impregnation method and characterized by surface area (BET), X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM) and X-ray photoelectron spectrum (XPS). The performance of adsorption and hydrogenation of nitrate was evaluated and compared with Al 2 O 3 , TiO 2 , and HZSM-supported Pd-Cu catalysts. The experimental results demonstrated that hydrotalcit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In our previous study, the performance of adsorption and hydrogenation of nitrate on hydrotalcite-supported Pd-Cu catalyst prepared by impregnation has been compared intensively with different supports (Al 2 O 3 , TiO 2 , and molecular sieve (HZSM)) catalysts at the same Pd-Cu loading [25]. The results demonstrated that hydrotalcite-supported Pd-Cu catalyst processed higher catalytic activity and selectivity.…”
Section: àmentioning
confidence: 99%
“…In our previous study, the performance of adsorption and hydrogenation of nitrate on hydrotalcite-supported Pd-Cu catalyst prepared by impregnation has been compared intensively with different supports (Al 2 O 3 , TiO 2 , and molecular sieve (HZSM)) catalysts at the same Pd-Cu loading [25]. The results demonstrated that hydrotalcite-supported Pd-Cu catalyst processed higher catalytic activity and selectivity.…”
Section: àmentioning
confidence: 99%
“…During the last ten years, some new methods/techniques used for the removal of nitrate ion from water have been investigated in China [61][62][63][64][65][66][67][68][69][70][71]. The methods include biological denitrification, bio-electrochemical denitrification and chemical denitrification.…”
Section: New Technologies For Nitrate Removalmentioning
confidence: 99%